Here is an interesting case of a problem in trigonometry...... I had encountered this in my CET entrance exam .....
The problem asks us to simplify. a[bcos(C)-c.cos(B)]. ......................(1).
Where a,b,c are sides of any triangle and A,B,C are its angles.
Using a= bcos(C)+c.cos(B). (Projection rule)
The expression (1) simplifies to
=b^2cos^2(C)-c^2cos^2(B)....... (2)
=b^2[1-sin^2(C)]-c^2[1-sin^2(B)]
=b^2-c^2-b^2sin^2(C)+c^2sin^2(B)............(3)
But sine rule says .....
bsin(C)=csin(B)
Implying that
b^2sin^2(C)=c^2sin^2(B)
Hence the expression (3) simplifies to
=b^2-c^2........ (4)
So far so good but comparing (4) with (2)
We may deduce cos^2(C)=1=cos^2(B)......
Implying C=B=90 degrees !!!!! .....( not a triangle!!)
Are you kidding ALGEBRA !!!!
Can you resolve the paradox????
Easy Math Editor
This discussion board is a place to discuss our Daily Challenges and the math and science related to those challenges. Explanations are more than just a solution — they should explain the steps and thinking strategies that you used to obtain the solution. Comments should further the discussion of math and science.
When posting on Brilliant:
*italics*
or_italics_
**bold**
or__bold__
paragraph 1
paragraph 2
[example link](https://brilliant.org)
> This is a quote
\(
...\)
or\[
...\]
to ensure proper formatting.2 \times 3
2^{34}
a_{i-1}
\frac{2}{3}
\sqrt{2}
\sum_{i=1}^3
\sin \theta
\boxed{123}
Comments
There are no comments in this discussion.